Recent Development of Natural Fibers Reinforced Polylactic Acid Composites - S.F.K. Sherwani; E.S. Zainudin; S.M. Sapuan; Z. Leman; A. Khalina (Journal of Research in Nanoscience and Nanotechnology, 2022)
The current research determines the most recent developments in natural fibres reinforced polylactic acid composites. Polylactic acid (PLA) is derived from renewable resources and is capable of degrading microorganisms, eliminating the pollution caused by petrochemical-based plastic. PLA is the most promising biodegradable material among biodegradable polymers since it is easily attacked by bacteria PLA decomposes easily, releasing H2O, CO2, and humus, the black material found in soil. PLA is a thermoplastic polymer that is widely used in the production of plastic bags, large planting cups, paper coating, fibres, films, packaging, and as a matrix material in composites. This review also discussed the physical and mechanical properties of several natural fibre reinforced polylactic acid composites. Several natural fibres have been used to reinforce PLA as a reinforcement for natural fibre composites in the field of composite manufacturing.